So let them burn - Cole, Kamilah (Cole, Kamilah. Divine traitors duology., 2024)
After her sister Elara forms an unbreakable bond with an enemy dragon, seventeen-year-old Faron, who once wielded the magic of the gods to save her island from those same dragon-riding colonizers, must find a way to save her sister and the fate of their world in the face of impossible odds.